Pengenalan sistem informasi akuntansi dan sistem pemasaran melalui sosial media dengan memperhatikan etika digital di lingkungan SMA Negeri 09 Pinrang - Sari, Fika Hartina; Cahyadi, Rahadian; Rahmawati, Rahmawati (STAI Auliaurrasyidin Tembilahan, 2024)
The community service program introducing accounting information systems and social media marketing at the high school level aims to enhance students' digital literacy in accounting and marketing. This initiative equips students with practical skills to manage financial information and ethically utilize social media for marketing activities. The program includes simulations of accounting applications, product marketing practices, and emphasizes digital ethics, such as safeguarding data security and complying with legal norms. The results demonstrate an increase in students' understanding of basic accounting information systems, digital marketing strategies, and the importance of digital ethics. This program is expected to provide students with relevant competencies to independently manage financial reports and address the challenges of the digital era.